ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN PELANGGAN PEMEGANG GARUDA FREQUENT FLYER TERHADAP FASILITAS PELAYANAN DI PT. GARUDA INDONESIA - Novita Wahyu Setyowati; Yanti Afianti (Universitas Bunda Mulia, 2017)
Through the results of a survey study of 70 (seventy) of respondents obtained research results, as follows : Tangible, Confidence, Reliability and empathy are considered valid and contribute positively to the value of R-Square = 98% and positive prediction, where the parameter estimators obtained , and significant. F-count value> F-table or 712.227> 2.557 for α = 0.05. Can be seen that the partial variable Tangible able to give effect to enhance customer satisfaction and are able to contribute positively and can serve as a strong indicator (value of R-Square = 80%). Positive predictions can be viewed via a probe parameters and significant. Value T-count> T-chart or 4.964> 1.7033 for the degrees of freedom (DF) α = 0.05.Confidence can be seen that the partial variables can give effect to enhance customer satisfaction and are able to contribute positively and can serve as a strong indicator (value of R-Square = 68%). Positive predictions can be viewed via a probe parameters and significant. Value T-count <T-table, or 1.55> 1.7033 for degrees of freedom (DF) α = 0.05.Reliability can be seen that the variable is able to give partial effect to enhance customer satisfaction and are able to contribute positively and can serve as a strong indicator (value of R-Square = 50%). Positive predictions can be viewed via a probe parameters and significant. Value T-count> T-chart or 3.934> 1.7033 for the degrees of freedom (DF) α = 0.05.Empathy can be seen that the partial variables can give the effect of increasing customer satisfaction and are able to contribute positively and can serve as a strong indicator (value of R-Square = 69%). Positive predictions can be viewed via a probe parameters and significant. Value T-count> T-chart or 4.111> 1.7033 for the degrees of freedom (DF) α = 0.05 Key Words Factor Tangible , Confidence , Reliability dan Empathy